2015
DOI: 10.1007/s00773-015-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

Sizing and energy management of a medium hybrid electric boat

Abstract: Fuel consumption is viewed as a fundamental problem in boats which are to operate on sea for a long time without need to refueling. In this paper, hybridization of a conventional medium-sized boat to reduce fuel consumption is considered. For this purpose, the optimal sizes for the main components, electric motor, internal combustion engine, and battery and generator are calculated via a constrained particle swarm optimization algorithm which considers accelerating and speeding expectations as the constraints.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…These design factors cause the fully installed energy density of lithium NMC battery packs to be around half of that for automotive battery packs -86 W h kg À1 for the Ellen Eferry vs. 160 W h kg À1 for a Tesla Model 3. 31,32 Because lithium NMC marine battery installations require so much compromise to be made safe, there is significant scope for using lower performance but safer chemistry to achieve similar or better overall performance. A good example is lithium iron phosphate (LFP), which has around 65% of the specific energy of NMC but is far safer and replaces expensive and problematic nickel and cobalt with highly abundant iron and phosphorous.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…These design factors cause the fully installed energy density of lithium NMC battery packs to be around half of that for automotive battery packs -86 W h kg À1 for the Ellen Eferry vs. 160 W h kg À1 for a Tesla Model 3. 31,32 Because lithium NMC marine battery installations require so much compromise to be made safe, there is significant scope for using lower performance but safer chemistry to achieve similar or better overall performance. A good example is lithium iron phosphate (LFP), which has around 65% of the specific energy of NMC but is far safer and replaces expensive and problematic nickel and cobalt with highly abundant iron and phosphorous.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…It was demonstrated that the strategy could be adapted to different hydrogen hybrid vessel sizes. In [80] a PSO algorithm was implemented for the component sizing, to reduce the fuel consumption, and a fuzzy logic controller was utilized for optimally splitting the energy between the diesel generators and the batteries. The proposed fuzzy-PSO method reduced the fuel consumption up to 40%, compared to the original conventional boat.…”
Section: Combined Optimal Design-control Studiesmentioning
confidence: 99%
“…Studying a series hybrid of a DC grid type, Soleymani et al (2015) optimised the sizing of the machinery. A particle swarm optimisation (PSO) algorithm was used for rightsizing a combustion engine, generator, electric motor and battery pack.…”
Section: Increasing the Frame Size In The Optimisation Problem: Solvimentioning
confidence: 99%
“…Sciberras and Grech (2012) and Sciberras and Norman (2012) studied a motor yacht with parallel topology to find an optimum solution between the two conflicting objectives of fuel consumption and physical size of the system. Instead of continuous scaling of the components as done by Soleymani et al (2015), the authors used a database of discrete components for a more reallife selection of available components. Using a rule-based control strategy, the control values for the components were set based on the velocity demand, battery SOC and the operating limits of the components.…”
Section: Increasing the Frame Size In The Optimisation Problem: Solvimentioning
confidence: 99%